Mitigar la propagación de la COVID-19: un desafío y una oportunidad (Ingeniería y Competitividad, 2020)
Dear Editor, The Colombian government declared the quarantine for all the population since 25th March, 2020 as a measure to mitigate the expansion of COVID-19 in the country. Nevertheless, this restrictive measure showed early some opposite consequences to its purpose. As observed in other countries, the restriction measure caused a mass purchase of products, formation of crowds in grocery, department stores and local markets. The fear of shortage also caused exhaustion of products, long journeys and accumulation of large numbers of people in stores, bank offices and ATMs.